Using Nursing Interventions to Increase the Breastfeeding - Ghadeer Ahmed Humaidi; Amenah Mohammed Almousa; Abdullah Mohammed Al-Balawi; Omar Fahad Buhaleem; Saleh Ibrahim Alfehaid; Saleh Radhi A Aladab; Howra Radhi A Almhasnah; Hamed Ali Saud Alali; Hassan Abdulmohsen Abdullah Al Ali; Jamila Mohammed Alhammad; Wejdan Mustafa Mohammed Aljuraydan; Hajer Ahmed Alhzoom; et al. (International Journal of Scientific Research and Innovative Studies, 2022)
Breastfeeding provides numerous health benefits for both infants and mothers. However, many women face challenges that lead to early cessation of breastfeeding. Nurses play a crucial role in supporting breastfeeding mothers and promoting successful breastfeeding outcomes. This mini-review explores nursing interventions aimed at increasing the duration of breastfeeding, focusing on evidence-based strategies to support and empower breastfeeding mothers.